Variability in runoff and responses to land and oceanic parameters in the source region of the Indus River. (July 2022) - Hussain, Azfar; Cao, Jianhua; Ali, Shaukat; Ullah, Waheed; Muhammad, Sher; Hussain, Ishtiaq; Rezaei, Abolfazl; Hamal, Kalpana; Akhtar, Mobeen; Abbas, Haider; Wu, Xiuqin; Zhou, Jinxing
Graphical abstract: Highlights: We assessed trends of runoff and its association with regional environmental parameters and Oceanic indices. Most sub-basins are experiencing significant increases in winter, while decreases in summer runoff. Annual runoff, precipitation, temperature, and NDVI increased, whereas, PET and NDSI declined. The oceanic indices shared a minimum correlation, than regional environmental factors. Abstract: Understanding the coherent variability of runoff in the Source Region of the Indus River (SRIR) with the regional environmental parameters (precipitation, temperature, potential evapotranspiration-PET, NDVI, NDSI), and global oceanic indices (El Niño Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), North Atlantic Oscillation (NAO), Arctic Oscillation (AO),  Indian Ocean Dipole (IOD) and Indian Summer Monsoon Index (ISMI) is of paramount importance. This study has attempted to show the relationship of the SRIR runoff with the regional meteorological and global oceanic indices. The monotonic Mann-Kendal, Sen Slope, and wavelet analysis were employed to assess the trends and periodicity in the hydro-meteorological variables. Monthly runoff from all sub-basins shows increasing trends from October to March and decreases from April to September, except for western tributaries. Most sub-basins in the SRIR are experiencing significant increases in winter while decreases in summer. The annual runoff trend suggests an increase after 2000 from the Kabul River Basin (KRB). However, contrasting results are evident in the Upper Indus Basin (UIB). The Jhelum River Basin (JRB) has shown a significant declining trend since the mid-1990s. Annual runoff (3.19 m 3 /s), precipitation (0.24 mm/year), temperature (0.011 °C/year), and NDVI (0.002) increased in the SRIR, whereas PET (−0.020 mm/year) and NDSI (−0.003) declined during 1970–2016. In general, built-up grassland, snow/ice, water bodies, and wetlands increased, while barren land, cropland, and forest/shrubland declined between 2001 and 2018. Overall, all the factors displayed a positive correlation with runoff. Generally, runoff has a stronger association with regional environmental factors than global, as evident in correlation and wavelet analysis, which implies that local factors had a more significant effect on runoff. However, NAO, AO, and ISMI shared a significant correlation other than the regional environmental factors concerning the oceanic indices. The warmer and wetter climate hastened the melting of snow/glaciers via runoff variation, and rising water inputs may have had a secondary impact on the SRIR. These findings have significant implications for decision-makers seeking to enhance water resource planning and operations in the SRIR in the context of future water management.